Economie de la décision publique et conflits d'usages pour un cadre de vie dans les espaces ruraux et périurbains - Philippe Jeanneaux (Développement Durable et Territoires)
Land-uses and neighbourhood conflicts reveal the rise of the rural living environment and with its confrontation with the other functions of the countryside (productive and "nature"). The thesis claimed in this article consists in defending the idea that land-uses conflicts mean as a deal with public decision-makers, taking into account the limits of the expression of the preferences by the voting procedure, and when exit is difficult. The focus is put on a French administrative territory: Puy de Dôme. The five year analysis (1998 to 2002) of litigation of the administrative court of Clermont-Ferrand, and the treatment by a local daily press La Montagne from 1999 to 2002, offer an explanation of different ways of right convened by opponents and the main ways to the material solutions brought to the disagreements.